Ultrastructural Changes in Human Trabecular Meshwork Tissue after Laser Trabeculoplasty - Jeffrey R. SooHoo; Leonard K. Seibold; David A. Ammar; Malik Y. Kahook (Journal of Ophthalmology)
Purpose. To compare morphologic changes in human trabecular meshwork (TM) after selective laser trabeculoplasty (SLT) and argon laser trabeculoplasty (ALT). Design. Laboratory evaluation of ex vivo human eye TM after laser trabeculoplasty. Methods. Corneoscleral rims from human cadaver eyes were sectioned and treated with varying powers of either SLT or ALT. Specimens were examined using light microscopy, scanning electron microscopy (SEM), and transmission electron microscopy (TEM). Results. TEM of SLT at all powers resulted in disrupted TM cells with cracked and extracellular pigment granules. SEM of SLT samples treated at high power revealed tissue destruction with scrolling of trabecular beams. SEM of ALT-treated tissue showed increasing destruction with exposure to higher power. The presence or absence of “champagne” bubbles during SLT did not alter the histologic findings. Conclusions. SLT-treated human TM revealed disruption of TM cells with cracked, extracellular pigment granules, particularly at higher treatment powers. Tissue scrolling was noted at very high SLT energy levels. ALT-treated tissue showed significant damage to both the superficial and deeper TM tissues in a dose-dependent fashion. Further studies are needed to guide titration of treatment power to maximize the IOP-lowering effect while minimizing both energy delivered and damage to target tissues.